Hydrogen production from wastewater: technology readiness, economic and environmental assessment, and scale-up challenges with mitigation strategies - Liang, Y. Y.; M. Shahabuddin, . (Elsevier, 2026)
Hydrogen production from wastewater can help meet the increasing demand for clean energy. This review shows that the amount of hydrogen produced varies depending on the kind of wastewater. It also points out that industrial streams have a higher potential than municipal or home sources. Studies show that producing hydrogen from wastewater can cost at least three times more than conventional methods. Electricity emissions significantly impact life cycle assessment (LCA) results, whereas stack cost and degradation prevail in techno-economic analysis (TEA) analysis. Wastewater-based hydrogen production technologies range from proof-of-concept to near-industrial readiness, with Aqueous Phase Reforming (APR) and Hydrothermal Liquefaction (HTL) being the most advanced but still facing scale-up challenges. Finally, we offer policy suggestions and outlooks for integrating wastewater into hydrogen energy systems.